The comparison of the effect of double and flat pyramid training methods on hypertrophy and muscular strength of male power-lifters - Mohammad Rasekh; Ramin Shabani (Physical Education of Students, 2021)
Background and Study Aim. Resistance training is considered as the most effective method to increase muscle strength and mass. The present study aimed to compare the effect of a double pyramid and a flat pyramid training methods on hypertrophy and muscular strength of male power-lifters.